Multidimensional Approach to Curriculum Transformation in Increasing Multicultural Appreciation - Supsiloani Supsiloani; Ratih Baiduri; Bakhrul Khair Amal; Sulian Ekomila (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
The need for curriculum transformation in Indonesia to support multicultural education is increasingly evident. This study focuses on how a multidimensional approach to curriculum transformation can effectively enhance students' appreciation of multiculturalism. This approach fosters tolerance and respect for cultural, ethnic, and religious diversity. This study used qualitative methods. Data were collected through in-depth interviews and documentation. Data analysis using thematic coding and triangulation techniques to ensure data validity, consistency, and reliability of findings. Curriculum transformation at State Junior High School I Medan integrates cognitive, affective, psychomotor, and socio-cultural dimensions to foster multicultural appreciation. Key changes include shifting the curriculum's focus from academic achievement to developing tolerance and respect for cultural diversity. Teaching materials now incorporate multicultural perspectives, and project-based participatory learning methods actively engage students in cultural activities. Classrooms are organized to promote gender and religious balance, and assessments are more holistic, evaluating students' academic performance and involvement in multicultural activities. This transformation creates a more inclusive and culturally responsive educational environment, helping students develop the academic and socio-emotional skills needed to live in a diverse society. This approach prepares students to be more tolerant and inclusive, positively impacting their interactions in an increasingly globalized world. This research provides valuable insights for educators and policymakers on increasing multicultural appreciation among students.